Botswana : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
Poverty and unemployment remained high in Botswana. The shortcomings of the labor market policies are responsible for a high unemployment rate. This selected issues paper sheds considerable light on ways that Botswana can enhance inclusive growth and reduce the high level of structural unemployment. Botswana was identified as having been able to sustain the highest economic growth compared with others in its league. Assessors suggest a prudent labor market for an overall sustained economic growth.